Do non-cognitive skills help explain the occupational segregation of young people? - Heather Antecol; Deborah A. Cobb-Clark (Institute for the Study of Labor (IZA), 2010)
This paper investigates the role of non-cognitive skills in the occupational segregation of young workers entering the US labor market. We find entry into male-dominated fields of study and male-dominated occupations are both related to the extent to which individuals believe they are intelligent and have male traits while entry into male-dominated occupations is also related to the willingness to work hard, impulsivity, and the tendency to avoid problems. The nature of these relationships differs for men and women, however. Noncognitive skills (intelligence and impulsivity) also influence movement into higher-paid occupations, but in ways that are similar for men and women. On balance, non-cognitive skills provide an important, though incomplete, explanation for segregation in the fields that young men and women study as well as in the occupations in which they are employed.
urn:nbn:de:101:1-201008116519
Keywords: J24; J16; J31; 330; non-cognitive skills; occupation; youth; gender